Peripheral Europe beyond the Troika: Assessing the "success" of structural reforms in driving the Spanish recovery - Luis Cárdenas; Paloma Villanueva; Ignacio Álvarez; Jorge Uxó González (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
Since 2014 the Spanish economy has recovered positive GDP growth, and the country has been growing well above the Eurozone average. This recovery has sparked an academic and political debate concerning the role that structural reforms, prescribed by the 'Troika', have played in peripheral Europe. For certain scholars and institutions, these structural reforms have allowed the market, through greater wage flexibility, to make the necessary adjustments to restore economic growth, resulting in a 'healthy' economic recovery. But, to what extent is this mainstream narrative solidly backed up by the empirical evidence? Can Spain be held up as an international example of the success of these reforms? The aim of this paper is to shed light on this debate. We consider that labor market reforms and wage devaluation policy are not the drivers of economic recovery. Instead, we offer an alternative explanation for recovery based on the theory of demand-led growth.
Keywords: E60; E12; J38; 330; Spain; demand-led growth; structural reforms; wage devaluation